Stock market responses to Covid-19: Evidence from Jakarta Islamic Index - Fianto, Bayu Arie; Nugroho, Perdana Adi; Ali Shah, Syed Alamdar; Busser, Rogier (Faculty of Economics, Universitas Islam Indonesia, 2024)
Purpose – This study examines the effect of Covid-19 in Indonesia on the value of abnormal returns, trading volume activity, and efficiency of the Jakarta Islamic Index (JII), the Indonesian Islamic stock market.Methodology – This study employed the event study model to measure the relationship between important events related to the Indonesian Covid-19 pandemic on stock returns and the stock trading volume of JII indexed companies. Using research analysis techniques in the form of a market-adjusted model, this study determines the period of events before, during, and after the event.Findings – This study found that the global Covid-19 announcement, announcement of the new normal, and announcement of the Covid-19 vaccination gave a significant abnormal return reaction to the JII index and did not provide a significant trading volume activity reaction. Implications – Indonesia's Islamic stock market, which falls into the semi-strong efficient category, responds quickly to important public information such as Covid-19-related announcements. Investors showed high sensitivity to major news, but trading volumes did not change significantly, indicating a cautious adjustment strategy. The different reactions across sectors, especially industry and energy, highlight the need for investor portfolio diversification. It is important for policymakers to provide clear and timely communication to maintain market stability during crises. Further research is required to understand the long-term impact and extend the coverage of international Islamic stock markets.Originality – This study examines several important Covid-19 events that occurred in Indonesia on stock returns and trading volumes in the Indonesian Islamic stock market.